Conflicts in Family Relations, Children's Emotions and Agency. (25th September 2017) - Notko, Marianne; Sevón, Eija
Abstract : What kind of conflicts and tensions do children experience with other children and adults in the family? Content analysis of 32 thematic interviews with 10‐ to 13‐year‐old children revealed that while conflicts often concern daily actions, tasks and routines, they also relate to decision‐making and fair treatment or to matters threatening the child's sense of emotional security. Parental conflicts and conflicts in child–parent relationships often arouse negative emotions that lead children to suppress their agency. However, conflicts, particularly those between siblings, may also open up possibilities for negotiation and agency.